2018
DOI: 10.19082/6417
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of psychomotor performance of driving among two kinds of shift work in Iran

Abstract: Background and aimDriving after a night shift imposes a risk on health care professionals and other road users. The aim of this study was to measure psychomotor performance of driving of night shift nurses compared to day-shift nurses.MethodsForty-seven volunteer female nurses working at Sina hospital in Tehran, Iran, with a call in all departments of hospital, participated in this study (23 night shift and 24 day shift nurses) in 2016. The tests included RT for simple reaction time, ATAVT for perceptual speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Although this study did not consider the risk of motor vehicle accidents between participants in the two groups of study, there has been documentation of incidents of motor vehicle accidents among night shift workers. A recent study in Iran made an alarming discovery of increased motor vehicle accidents among night shift workers (Saadat et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although this study did not consider the risk of motor vehicle accidents between participants in the two groups of study, there has been documentation of incidents of motor vehicle accidents among night shift workers. A recent study in Iran made an alarming discovery of increased motor vehicle accidents among night shift workers (Saadat et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, researchers have found that the impairment of individuals who drive while fatigued mirrors the impairment that occurs when driving while intoxicated. Furthermore, mounting evidence suggests that being awake for 18 hours or more results in the same level of impairment as someone having a blood alcohol content of 0.05% (Geiger-Brown & McDonald, 2021;Saadat et al, 2018;"Practice Safe Driving," 2017). The legal blood alcohol content level limit in all 50 U.S. states is 0.08% (U.S. Department of Transportation, NHTSA, n.d.).…”
Section: Bureau Of Labor Statistics [Bls] 2022)mentioning
confidence: 99%